Controlling the Microstructure of Conjugated Polymers in High‐Mobility Monolayer Transistors via the Dissolution Temperature. (20th November 2019) - Li, Mengmeng; Bin, Haijun; Jiao, Xuechen; Wienk, Martijn M.; Yan, He; Janssen, René A. J.
Abstract: It remains a challenge to precisely tailor the morphology of polymer monolayers to control charge transport. Herein, the effect of the dissolution temperature ( T dis ) is investigated as a powerful strategy for morphology control. Low T dis values cause extended polymer aggregation in solution and induce larger nanofibrils in a monolayer network with more pronounced π–π stacking. The field‐effect mobility of the corresponding monolayer transistors is significantly enhanced by a factor of four compared to devices obtained from high T dis with a value approaching 1 cm 2 V −1 s −1 . Besides that, the solution kinetics reveal a higher growth rate of aggregates at low T dis, and filtration experiments further confirm that the dependence of the fibril width in monolayers on T dis is consistent with the aggregate size in solution. The generalizability of the T dis effect on polymer aggregation is demonstrated using three other conjugated polymer systems. These results open new avenues for the precise control of polymer aggregation for high‐mobility monolayer transistors. Abstract : Coole Sache : Die Auflösungstemperatur ist ein effizienter Parameter zur Kontrolle der Aggregation konjugierter Polymere in Lösung und beeinflusst ihre Mikrostruktur in Monolagen. Eine niedrigere Auflösungstemperatur verursacht stärkere π‐π‐Stapelwechselwirkungen und größere Faserdomänen, wodurch sich Hochleistungs‐Monolagentransistoren mit einer Mobilität von annähernd 1 cm 2 V −1 s −1 ergeben.